2018
DOI: 10.1002/ecs2.2532
|View full text |Cite
|
Sign up to set email alerts
|

Is being familiar with biodiversity related to reasoning about ecology?

Abstract: Many science educators believe that student recognition of biodiversity is an important precursor to discovering patterns and understanding processes that define and shape ecological systems. We investigated (1) the total number, taxonomic categories, specificity, and diversity of backyard organisms that middle (MS) and high school (HS) students and teachers named, (2) how the number, specificity, and diversity of organisms that students and teachers named related to their overall performance on an ecology lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Eventually, students wrongly concluded that they could classify animals of different species but of the same family or the same order into the same species. Le, et al (2018) found that lower-secondary school students face real obstacles when classifying even most known animals (geese, butterflies, crocodiles, etc.). These obstacles are often misconceptions and are poorly treated and reformulated in the teaching-learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, students wrongly concluded that they could classify animals of different species but of the same family or the same order into the same species. Le, et al (2018) found that lower-secondary school students face real obstacles when classifying even most known animals (geese, butterflies, crocodiles, etc.). These obstacles are often misconceptions and are poorly treated and reformulated in the teaching-learning process.…”
Section: Discussionmentioning
confidence: 99%
“…First, such assessments tend to be rather removed from the process of identifying living organisms under field conditions, often for example using static images or drawings. Second, they have tended to be at the species level, rather than higher taxonomic or other groupings, although people's knowledge is often poorer at the species level (Gosler & Tilling, 2022; Le et al., 2018). Third, and making them more relevant to personalized ecologies, they have tended to focus on species that are native to the broad area or country in which the people being assessed reside (rather than concerning species drawn from a global pool).…”
Section: Internal Factorsmentioning
confidence: 99%
“…As a Thomas Henry Huxley review, I will focus predominantly on direct interactions between people and other animals. The full personalized ecology of an individual person is obviously much broader, although many people tend actually to be more aware of animals than plants, and indeed may pay very little heed to plants, giving rise to the phenomenon of ‘plant‐blindness’ in many urban and higher income societies (Balding & Williams, 2016; Le et al., 2018; Stagg & Dillon, 2022); such ‘blindness’ doubtless applies also to many other non‐animal and animal groups. Amongst animals, people seem particularly to be aware of birds, arguably because these are virtually ubiquitous (occurring in most environments), predominantly day active and reliant on vision, large bodied (by animal standards) and often mobile, appear diverse in colour and form to human vision, are vocal and typically at frequencies to which human hearing is sensitive, exhibit an array of observable behaviours, often only flee at relatively short distances from potential threats (including people), and are relatively very well known (Gaston, 2022).…”
Section: Introductionmentioning
confidence: 99%